THE EFFECTIVENESS OF SURGICAL TREATMENT OF PELVIC ORGAN PROLAPSE IN WOMEN IN THE TRANSITION PERIOD - Вадим Гельевич Мозес; Наталья Евгеньевна Мезенцева; Марина Анатольевна Ющенко; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Кира Борисовна Мозес; Наталья Степановна Черных; Яэль Центер (The Publishing House Medicine and Enlightenment, 2023)
Purpose - to evaluate the impact of surgical correction of pelvic organ prolapse on the quality of life of patients in the transition period according to the STRAW+10 classification. Materials and methods. 20 patients in the transitional period according to the STRAW+10 classification with pelvic organ prolapse (POP) requiring surgical treatment were studied by a continuous method. All patients underwent surgical correction of prolapse with a mesh implant using transvaginal access with transobturator fixation, levatoroplasty. Efficacy was evaluated after 6 months: the assessment of quality of life was studied using the PFDI-20 questionnaire. Results. The study demonstrates the effectiveness of surgical correction of POP in women of transitional age - after 6 months of the postoperative period, there was a statistically significant decrease in the intensity of POP symptoms and an improvement in some criteria of quality of life: the POPDI pelvic organ prolapse scale and the overall PFDI-20 value. At the same time, it should be recognized that these conclusions are limited by the design of the study.